Manajemen Customer Relations Kantor Pertanahan Kota Bandung - Bakti, Well Vira Dela Cita; Wahyudin, Aep; Astuti, Dyah Rahmi (Reputation: Jurnal Ilmu Hubungan Masyarakat, 2024)
This research aims to describe customer relations through the concept of customer relationship management at Bandung City Land Office, including planning, people, and process in effort to provide the best service to customers. The research used descriptive method. The descriptions based on data obtained from informants, namely the Bandung City Land Office. The result showed customer relations management by Bandung City Land Office, began stage 1) planning through communicator image planning, front office image planning, and institutional image planning, 2) people through the implementation of activities to improve relations within the internal institution as well as the development and capacity development of Human Resources, and 3) process includes the implementation that has been carried out, namely the application of handling complaints, quality of service, giving attention and care to customers, as well as evaluation to measure the achievement of services.